What Matters for Financial Development and Stability? - Almarzoqi, Raja (IMF Working Papers; Working Paper, 2015)
This study aims to identify policies that influence the development of financial institutions as measured across three dimensions: depth, efficiency, and stability. Applying the concept of the financial possibility frontier, developed by Beck and Feyen (2013) and formalized by Barajas et al (2013a), we determine key policy variables affecting the gap between actual levels of development and benchmarks predicted by structural variables. Our dynamic panel estimation shows that inflation, trade openness, institutional quality, and banking crises significantly affect financial development. Our analysis also helps identify potential complementarities and trade-offs for policy makers, based on the effect of the policy variables across the different dimensions of financial development.